2020
DOI: 10.31234/osf.io/evp8b
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is Discrimination Widespread? Testing Assumptions about Bias on a University Campus

Abstract: Discrimination has persisted in our society despite steady improvements in explicit attitudes toward marginalized social groups. The most common explanation for this apparent paradox is that due to implicit biases, most individuals behave in slightly discriminatory ways outside of their own awareness (the dispersed discrimination account). Another explanation holds that a numerical minority of individuals who are moderately or highly biased are responsible for most observed discriminatory behaviors (the concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Interventionists often assume that they can change organizational culture by changing the hearts and minds of individuals in that organization. Yet what targets of bias often report is not a series of unrelated biased episodes but episodes that reveal patterns of BIASes embedded in a culture and perpetuated by social norms (Markus & Kitayama, 2010), albeit enacted by a minority of people (Campbell & Brauer, 2020). Thus, efforts to counteract biased behavior at scale hinge on changing the cultural context.…”
Section: Systemic Bias: From Individual Minds To Cultural Normsmentioning
confidence: 99%
“…Interventionists often assume that they can change organizational culture by changing the hearts and minds of individuals in that organization. Yet what targets of bias often report is not a series of unrelated biased episodes but episodes that reveal patterns of BIASes embedded in a culture and perpetuated by social norms (Markus & Kitayama, 2010), albeit enacted by a minority of people (Campbell & Brauer, 2020). Thus, efforts to counteract biased behavior at scale hinge on changing the cultural context.…”
Section: Systemic Bias: From Individual Minds To Cultural Normsmentioning
confidence: 99%
“…We also know very little about how widespread different kinds of intergroup behaviors are. We know that individuals belonging to marginalized groups are treated more negatively on average but usually do not know what percentage of the population is actually responsible for negative intergroup behavior (Campbell & Brauer, 2019). For example, the average scientist evaluates female candidates for a lab-manager position more negatively than equally qualified male candidates (Moss-Racusin et al, 2012), but we do not know whether this bias is due to a numerical majority of scientists’ slight preferences for men or to a numerical minority of scientists who systematically prefer the male candidate.…”
Section: Unanswered Questions: a Possible Agenda For Prejudice Researchmentioning
confidence: 99%
“…A similar reasoning can be applied to research examining how different groups differ in readiness to change their intergroup behaviors. Groups of individuals with high scores on motivational measures (e.g., internal motivation to respond without prejudice; Plant & Devine, 1998) or who are strongly committed to diversity (Campbell & Brauer, 2019) are likely to be willing to change their behavior. It is unclear, however, how different segments compare in terms of ability to change their behavior.…”
Section: Unanswered Questions: a Possible Agenda For Prejudice Researchmentioning
confidence: 99%
“…A large-scale campus climate survey was conducted while we were holding focus groups (total N = 8,652; Campbell and Brauer, 2020a). The results of this survey showed that 18% of students of color had personally experienced hostile, harassing or intimidating behavior compared to 11% of white students, which is consistent with the finding from focus groups that these incidents did occur, but were less common than often assumed and not the primary factor determining the sense of belonging among students of color.…”
Section: Quantitative Data Gatheringmentioning
confidence: 99%
“…Finally, we ran a series of observational field experiments to determine how members of marginalized social groups were treated compared to non-marginalized peers across a series of subtle behaviors (Campbell and Brauer, 2020a). We reasoned that although experiences of overt discrimination may be propagated by a small proportion of students with extreme views, slightly negative treatment of individuals from marginalized backgrounds could be widespread among individuals.…”
Section: Observational Data Gatheringmentioning
confidence: 99%